Politik Pembangunan Koeksistensi di Kota Depok: Refleksi Kasus Demonstrasi terhadap Kapel Gereja Bethel Indonesia (GBI) Cinere oleh Organisasi Masyarakat - Simamora, Naufal Bariq Alauddin; Ridwan, Ridwan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The demonstration at the GBI Cinere Chapel in September 2023 was one of the factors that made Depok City the city with the lowest tolerance index in Indonesia. The city of Depok has had the lowest tolerance index in Indonesia since 2020-2023, so it is included in the category of intolerant city. This research aims to explore political steps that can be used to build coexistence among the people of Depok City in the challenges that arise in achieving coexistence amidst the complexity of diversity, especially in the case of the GBI Cinere Chapel demonstration. The method used in this research is a qualitative-descriptive method by analyzing descriptive data obtained through interviews and writing and making observations from the data. The results of the research show that in carrying out coexistence development efforts in the Depok City community, we must be active in collaborating with leadership and community dialogue, reviewing legal and policy frameworks, as well as adapting the practices of tolerance development programs. Thus, it is hoped that these various efforts can become preventive efforts in maintaining unity in the Depok City community.